(untitled) (Annals of Medical Research, 2021)
Aim: Aim of the study is to demonstrate impact of health news at social media on the health perception of society, among healthcare related and non-healthcare related participants, under the subheadings of reliability of that news, doctor-patient relationship, patient health attitudes and health advertising and marketing. Social media has some benefits on health communication such as more accessible, shared health information; but also has some limitations such as lack of reliability, confidentiality, and privacy. Thereby misinformation through these platforms may lead the society to gain wrong health attitudes.Material and Methods: This was a cross-sectional survey study consisted of two sections. First section was based on the demographic data and second section consisted of 25 questions about the attitudes related to social media and internet news to be answered using the Likert scale. Statistical analysis was performed using the Statistical Package for the Social Sciences version 22.0. Responses of the survey compared between the healthcare related and non-healthcare related participants by using Mann-Whitney U test P-value less than 0.05 was considered statistically significant.Results: Among 1,622 returned valid questionnaires %66.8 of the participant were healthcare related. For all subheadings responses were significantly different among healthcare related and non-healthcare related participants (p 0.05 for all circumstances).Conclusion: This survey demonstrated that perception attitudes of the society formed by health content shares on social media were significantly different between the groups. It could be mentioned that healthcare related population was more conservative and had a critical approach on this issue, on the other hand non-healthcare related population more frequently impressed by that kind of shares and tend to accept them directly. So raising awareness about digital health literacy is a public health necessity to ensure the access to valid and reliable information.